Comparative Analysis: Influence of Interest Rates on Returns of Real Estate Private Equity Index and Real Estate Public Equity Index - Sharma Manu (Real Estate Management and Valuation, 2022)
In this paper, we studied the influence of interest rates on a US-based real estate private equity index as well US Wilshire public equity REIT Index. The interest rates that are chosen as independent variables include Monthly LIBOR, Yearly LIBOR and the Federal Cost of Funds Index. The dependent variables include US-based real estate private equity index that includes quarterly returns of 1,035 real estate funds, including liquidated funds formed between 1986 and 2018. The other dependent variable is the US Wilshire REIT Index. The variance of returns of interest rates considerably influences the variance of returns of the US PERE Index, whereas variance of returns of interest rates doesn’t influence the variance of returns of the US Wilshire REIT Index. Also, the real estate index is positively correlated to interest rates and so rising interest rates influence the returns of US PERE Index in a positive manner. The study shows that private equity real estate investors should expect higher return as the cost of funds increase.